Illicit Drug Trends Globally - Vandam, L.; Matias, J.; McKetin, Rebecca; Meacham, M.; Griffiths, P. (2016)
© 2017 Elsevier Inc. All rights reserved. Human consumption of psychoactive substances goes back to prehistory and has always been a global phenomenon even if patterns of use and prevalence rates vary considerably by time and place. The concept of problematic drug use, and concerns about how this should be defined and measured, is, however, a more recent development and until recently mostly associated with a restricted number of Western industrialized countries. This has changed and with increasing globalization drug problems are now both more relevant to, and more recognized in, low- and middle-income countries. Demographic factors also mean that the most significant public health implications of substance misuse are already probably impacting most on the developing rather than the developed world. This article reviews the methodological approaches that are commonly used to monitor the normally hidden behavior of drug use and associated risks and reviews the global and regional structures that exist for undertaking this task. An overview is also provided for the main types of illicit drugs and their places on the global scene, with links to data sources to allow the reader access to more up-to-date information as it becomes available.